Trocas gasosas foliares de espécies de plantas leguminosas e não-leguminosas cultivadas em ambiente semiárido - Ferreira, Jean Telvio Andrade (2020)
The Região semiarid region due to its climatic characteristics can make the plants behave in different ways according to the conditions of the environment and with different responses throughout the day. The objective of the work was to evaluate leaf gas exchange using the daily course method of leguminous and non-leguminous plants in the semi-arid region of Paraíba in an experiment with three randomized blocks and ten treatments (Crotalaria juncea L., C. spectabilis Roth, C. ochroleuca G. Don., Canavalia ensiformes (L.) DC., Dolichos lablab L., Mucuna pruriens (L.) DC., Neonotonia wightii (Wight & Arn.) J.A. Lackey e Brachiaria decumbens Stapf), Pennisetum americanum (L.) R.Br.), Stilozobium aterrimum Piper and Tracy. Assessments were made using the daily course method, successively at the hours of 8: 00-10: 00, 10: 00-12: 00, 12: 00-14: 00,14: 00-16:00 and 16:00 -18: 00 hours. The variables analyzed were for temperature, stomatal conductance, internal concentration of carbon dioxide, relationship between internal and external concentration of carbon dioxide, net CO2 assimilation, transpiration, water use efficiencies, intrinsic use of water and carboxylation as a function of evaluation and species schedules. The species C. juncea, C. ochroleuca and C. spectabilis of the Fabaceae family showed the highest values for net CO2 assimilation in the environmental conditions of the area, the hours 8: 00-10: 00 and 10: 00-12: 00 higher values in the liquid assimilation rate, the species B. decumbens, P. americanum and C. juncea were more efficient in the use of water.